MAPPING THE ORGANIZATIONAL CHANGE LANDSCAPE: A SYSTEMATIC LITERATURE REVIEW OF CHANGE CLASSIFICATIONS AND THEIR CHARACTERISTICS - Yesika Isma W; Anang Kistyanto; Jun Surjanti; Dwiarko Nugrohoseno (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This research aims to map and combine modern typologies and definitions of organizational change based on a systematic literature review (SLR) in Scopus-registered literature from 2015 to 2025. Utilizing the PRISMA 2020 protocol, twenty research papers were thematically analyzed to understand conceptual trajectories and typological shifts in the literature on organizational change. The analysis identifies five distinct and broad typologies of change consisting of planned, emergent, incremental, transformational, and adaptive/hybrid, with flares to their boundaries. This study highlights a shifting paradigm towards adaptive and learning-based model from control and linear, to agility, digital transformation and resilience. Through the conceptual integration of classical and contemporary typologies and definitions, organizational change is shifted from being one discrete event to a continuous strategic capability. This review provides an elaborate conceptual mapping that draws the most theoretical learning and implications for adaptive leadership and sustainable organizational development.